An Intention-Aware Agent Framework for Multi-Agent Decentralized Partially Observable Environments - Bhaskar Trivedi; Manfred Huber (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
In the real world, humans often collaborate with others without direct communication. To do this successfully, they have to infer their intentions and choose actions that complement the predicted actions of their collaborators to perform the task efficiently. Since the peer’s state and action are generally not directly observable, these are usually estimated based on environmental change and then used to predict the intention. While humans can achieve this easily, this form of collaboration is difficult for artificial intelligent agents operating in partially observable environments, leading to agent architectures that do not attempt to explicitly infer other agents’ intentions but rather rely on additional knowledge or reactive collaboration, relying on the steady state character of other agents. In this paper, we propose an agent model that explicitly defines and utilizes estimates of other agents’ intentions to yield more effective collaboration in decentralized partially observable domains, where each agent’s knowledge of and current belief state in the environment can be different. The resulting agents explicitly estimate other agents’ intentions from their observations and utilize these estimates in a Reinforcement Learning process on a modified Dec-POMDP model to learn collaborative strategies. Initial experiments in a simple, partially observable collaborative manipulation domain show the ability of these intention-aware agents to learn optimal hierarchical strategies faster and more stably than equivalent agents without intention awareness.